PENGARUH GREEN MARKETING DAN MARKETING MIX TERHADAP CUSTOMER PREFERENCE DAN DAMPAKNYA TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Mahasiswa S2 Konsumen Aqua-Danone, Fakultas Ilmu Administrasi Universitas Brawijaya. Malang) - Riswati, Any; Suharyono, Suharyono; Kumadji, Srikandi (FIA UB, 2015)
Green marketing is the concept of green marketing that is friendly to nature and environmental sustainability, green marketing is defined as a management process responsible for identifying, anticipating and satisfying the needs of consumers is profitable and sustainable (Peattie, 1992). Aqua Danone uses green marketing strategy as environmentally friendly marketing strategy shaft successful, because aqua have an environmental policy